First experience of implementing Candida auris real-time PCR for surveillance in the UK: detection of multiple introductions with two international clades and improved patient outcomes. (September 2022) - Taori, S.K.; Rhodes, J.; Khonyongwa, K.; Szendroi, A.; Smith, M.; Borman, A.M.; Kumarage, J.; Brown, C.S.; Moore, G.; Desai, N.
Summary: Background: Candida auris has been associated with rapid transmission and high mortality. A novel PCR-based surveillance programme was initiated at a London teaching hospital from January 2018. The results of this implementation until March 2019 are presented along with the clinical, transmission and phylogenetic characteristics encountered in that setting. Methods: A real-time PCR assay for C. auris was developed, validated, and implemented for direct use on skin swabs and urine. Environmental swabs were also tested by PCR as an emergency outbreak-control measure. Clinical risk factors and outcomes of patients were determined. Environmental dispersal was assessed using 24 h settle plate cultures around nine colonized patients followed by air sampling around one colonized patient during high- and low-turbulence activities. Sequencing was performed using Illumina HiSeq and maximum likelihood phylogenies were constructed using rapid bootstrap analysis. Results: Twenty-one C. auris colonized patients were identified. Median turnaround time of colonization detection reduced from 141 h (5.8 days) to approximately 24 h enabling rapid infection-control precautions. Settle plates detected 70–600 cfu/m 2 around colonized patients over 24 h and air sampling suggested dispersal during turbulent activities. C. auris DNA was detected from 35.7% environmental swabs. Despite being in a high-risk setting, no patients developed invasive infection. Sequencing analysis of isolates from this centre identified two introductions of the South Asian (Clade I) and one of the South African (Clade III) strain. Conclusion: The PCR offers a rapid, scalable method of screening and supports clinical risk reduction in settings likely to encounter multiple introductions.